Postural relief of dyspnoea in severe chronic airflow limitation: relationship to respiratory muscle strength. - O'Neill, S (1983)
Maximal static inspiratory and expiratory pressures (Pimax and Pemax) were measured in six different positions in 40 patients with advanced chronic airflow limitation and in 140 normal subjects to determine whether posture influences respiratory muscle strength. Patients with chronic airflow limitation were studied on days 1 and 5 of an acute exacerbation. There was no postural effect on maximal static pressures in the normal subjects. We divided our patients with chronic airflow limitation into "moderate" and "severe" groups on the basis of a Pimax in the standing position greater or less than 35 cm H2O. The seated leaning-forward position was the preferred posture in 22 of the 23 "severe" patients and 13 of the 17 "moderate" patients. Pimax was greater in the seated leaning-forward position than in the other positions studied (p less than 0.001) on days 1 and 5 in the "severe" patients and (p less than 0.05) on day 5 in the "moderate" patients. Posture had no influence on Pemax in patients with chronic airflow limitation. There was a significant improvement in both Pimax (p less than 0.01 for the "severe" group and p less than 0.05 for the "moderate" group) and Pemax (p less than 0.01 for both groups) between days 1 and 5. The seated leaning-forward position was the optimum posture for the patients to generate maximum inspiratory pressures and to obtain greatest subjective relief of dyspnoea.